2015
DOI: 10.1007/s12288-015-0517-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbon Dioxide Insufflation Applied at Different Pressures and Periods on Thrombotic Factors

Abstract: The aim of this experimantal study which is applied on rats, is to determine the differences on the clotting factors over the application of low and high intraabdominal pressure (IAP) values in different periods of time in carbon dioxide (CO 2 ) pneumoperitoneum. Thirty rats were randomized into five groups (n = 6): a control group (Group K) and 1 h and 6 mm Hg IAP (Group A), 2 h and 6 mm Hg IAP (Group B), 1 h and 12 mm Hg IAP (Group C) and 2 h and 12 mm Hg IAP were created with CO 2 pneumoperitoneum (Group D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Among the benign disorders, Dubey et al [6] investigate how life-saving intra-uterine blood transfusions to Rh-negative fetuses of Rh-positive mothers may carry the risk of inducing additional maternal antibodies against fetal antigens, thereby aggravating Rhisoimmunization. Sen et al [7] similarly caution that highpressure carbon dioxide insufflation, commonly used in laparoscopic surgeries, may depress natural anticoagulant systems as well as fibrinolysis thus contributing to surgeryassociated thrombophilia.…”
mentioning
confidence: 99%
“…Among the benign disorders, Dubey et al [6] investigate how life-saving intra-uterine blood transfusions to Rh-negative fetuses of Rh-positive mothers may carry the risk of inducing additional maternal antibodies against fetal antigens, thereby aggravating Rhisoimmunization. Sen et al [7] similarly caution that highpressure carbon dioxide insufflation, commonly used in laparoscopic surgeries, may depress natural anticoagulant systems as well as fibrinolysis thus contributing to surgeryassociated thrombophilia.…”
mentioning
confidence: 99%
“…Sen et al carried out a randomized study on rats divided into 4 different groups, respectively group A exposed to 6 mmHg of pressure for 1 hour, group B exposed to 6 mmHg of pressure for 2 h, group C exposed to 12 mmHg of pressure for 1 hour, group D exposed to 12 mmHg of pressure for 2 h. The study showed evidence of hyperactivation of coagulation in the groups subjected to high pressure and for a longer time, demonstrated by an increase in its factors and in fibrinogen, and a reduced activity of the fibrinolytic system [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same occurs in the lung submitted to a regime of non-physiological pressure levels, which further accentuates the change in homeostasis. Inflammatory factors caused by the surgery trauma, PNP pressure, and mechanical ventilation promote the formation of these ROS, time-exposure dependent [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Os genogrupos I, II e IV compreendem os genótipos encontrado em seres humanos. As infecções pelo GI e GII são responsáveis pela maioria das doenças em humanos, enquanto as infecções associadas pelo genótipo GII.4 ocorrem com maior frequência e apresentam-se como uma das maiores causas das gastroenterites epidêmicas ou esporádicas (28,53,43,61,97) . O genogrupo GIII inclui vírus identificados em bovinos (73) , enquanto aqueles identificados em suínos estão classificados no genogrupo GII (90,99) .…”
Section: Classificaçãounclassified